2004
DOI: 10.1590/s0037-86822004000200010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the phagocytic activity of peripheral blood monocytes of patients with Jorge Lobo's disease

Abstract: Studies on host-parasite interaction in Jorge Lobo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…Changes in lymphocyte surface markers and proliferation were accompanied by reduced antibody titers to common marine microorganisms. No evidence for impaired phagocytosis in monocytes and granulocytes obtained from dolphins with lobomycosis was found, compatible with a report that phagocytosis of L. loboi by monocytes from human patients did not differ from controls (Vilani-Moreno et al 2004b). Despite evidence that humans and dolphins have substantial defects in cell-mediated immunity, it remains unclear whether infection with Lacazia represents an opportunistic infection or whether infection leads to secondary changes in immune function (Reif et al 2009, Honda andRaugi 2013).…”
Section: Risk Of Zoonotic Transmission Of Lobomycosissupporting
confidence: 76%
“…Changes in lymphocyte surface markers and proliferation were accompanied by reduced antibody titers to common marine microorganisms. No evidence for impaired phagocytosis in monocytes and granulocytes obtained from dolphins with lobomycosis was found, compatible with a report that phagocytosis of L. loboi by monocytes from human patients did not differ from controls (Vilani-Moreno et al 2004b). Despite evidence that humans and dolphins have substantial defects in cell-mediated immunity, it remains unclear whether infection with Lacazia represents an opportunistic infection or whether infection leads to secondary changes in immune function (Reif et al 2009, Honda andRaugi 2013).…”
Section: Risk Of Zoonotic Transmission Of Lobomycosissupporting
confidence: 76%
“…These patients have shown absence of response to dinitrochlorobenzene, as well as delayed responses to Staphylococci , Streptococci , Trycophyton and Candida antigens, but a high reactivity to mycobacterial antigens 28,34 . Leucocytic activity, specifically neutrophil function, as well as complement system activity, is normal 35,36 . This is not unexpected as it has been shown that L. loboi has the capacity of activating complement system by its alternate pathway 34,36 .…”
Section: Aetiology and Pathologymentioning
confidence: 72%
“…35,36 This is not unexpected as it has been shown that L. loboi has the capacity of activating complement system by its alternate pathway. 34,36 Humoral immunity studies reveal that Lobomycosis patients show a predominantly Th2 lymphocyte subpopulation cytokine profile, 28,34 which could also negatively modulate its Th1 cellular counterpart. In attempt to measure intradermal reactivity in carrier cases, an antigen called Lobina was developed but unfortunately, it was not adequately specific as it showed cross reactivity with Paracoccidioides and Mycetomas.…”
Section: Aetiology and Pathologymentioning
confidence: 84%
See 1 more Smart Citation
“… 37 The leukocyte and neutrophil functions, as well as complement activity, are preserved in patients with Jorge Lobo’s disease. 38 , 39 Studies of humoral immunity in patients with lobomycosis exhibit a Th2 cytokine profile with increased production of IL-4 and IL-6 and lower production of IL2. 28 , 35 , 40 Some authors believe in a protective factor caused by the presence of the melanin within the fungus wall.…”
Section: Introductionmentioning
confidence: 99%